Adult mental health clinicians' perspectives of parents with a mental illness and their children: single and dual focus approaches - Phillip Tchernegovski; Rochelle Hine; Andrea E. Reupert; Darryl J. Maybery (BMC, 2018)
Abstract Background When clinicians in the adult mental health sector work with clients who are parents with dependent children, it is critical they are able to acknowledge and respond to the needs of the parents and their children. However, little is known about clinicians' personal perspectives and reactions towards these parents and children or if/how they balance the needs of both. Methods Semi structured interviews were conducted with eleven clinicians from adult mental health services in Australia. Interviews focused on clinicians' experiences when working with parents who have mental illness. Transcripts were analysed within an Interpretative Phenomenological Analysis framework to examine participants' perspectives and personal reactions to parents and children. Results There was considerable divergence in participants' reactions towards parents and children and the focus of their perspectives when working with parental mental illness. Feelings of sympathy and responsibility made it difficult for some participants to maintain a dual focus on parents and children and contributed to some adopting practices that focused on the needs of parents (n = 3) or children (n = 1) exclusively. Other participants (n = 7) described strategies and supports that allowed them to manage these feelings and sustain a dual focus that incorporated the experiences and needs of both parents and children. Conclusions It is difficult for some mental health clinicians to maintain a dual focus that incorporates the needs and experiences of parents and their children. However, findings suggest that the challenges of a dual focus may be mitigated through adequate workplace support and a strengths-based practice framework that emphasises parental empowerment.